Epidemiology of Hepatitis B and C Infections in Al-Anbar/Iraq and Correlation Between Viral Load and Liver Function - Mohammed A. Hamad; Ala’a F. Habeeb; Nabaa A. Muhammed; Rawaa A. Muhammed (Advances in Virology)
Conclusion: The study concluded that females have a higher rate of infection with higher progression of the HBV and more morbid liver enzymes. The highest affected age groups are the highest communicational and economic activity group of young adults with elevated impact on the liver with HCV viral load increasing.